Semibatch Aqueous-Solution Polymerization of Acrylic Acid: Simultaneous Control of Molar Masses and Reaction Temperature - Minari, Roque Javier (2011)
The semibatch polymerization of non-ionized acrylic acid (AA) was investigated with the aim of producing poly(acrylic acid) (PAA) of controlled molar masses, at complete AA conversion, and under safe conditions. The proposed strategy mainly consists in feeding the AA at a constant rate along the reaction, for simultaneously controlling polymerization rate and molar masses. PAA of intermediate Mn, in the range 1x104–2x105 g .mol-1, was produced through an adequate selection of both the initiator concentration and the AA flow rate. In all experimental conditions, backbiting reactions were confirmed by 13C NMR. A simple mathematical model was developed to help interpret the experimental results.